Dynamics of anthropogenic pollution of the Glubokaya River in the Rostov Region - O. V. Dymnikova; A. E. Borman (Безопасность техногенных и природных систем, 2022)
Introduction. The article deals with the problems of deterioration of water quality in rivers in the Rostov region, their shallowing and drying out. The degradation of reservoirs is associated with various aspects of economic and industrial anthropogenic activities. The degree of influence depends on the intensity of the negative impact, and can be reduced if environmental measures are implemented.Problem Statement. The objective of this study is to monitor the water quality of the Glubokaya River in the Rostov region on different sections of the river and to assess the degree of anthropogenic impact.Theoretical Part. Water quality studies were carried out in three channels of the Glubokaya River on the territory of the cities of Millerovo and Kamensk-Shakhtinsk, as well as near them. The content of ammonia, phosphorus was determined by spectrophotometric analysis methods and petroleum products by IR photometric analysis method. The results of the study of water quality in the reservoir are compared with the normative values for three years with a certain periodicity.Conclusions. The results of the studies on changes in the chemical composition of water at various sites in dynamics, taking into account the degree of anthropogenic load, are analyzed.